COUNTER-NARRATIVES WITHIN POWER DISCOURSE IN ELECTORAL PRACTICE: A FOUCAULDIAN ANALYSIS OF THE 2024 BANTEN GUBERNATORIAL ELECTION - Alamsyah, Alamsyah; Udi Rusadi; Frengki Napitupulu; Irwanti, Marlinda (Bajang Institute, 2026)
This study examines the role of counter-narratives in the discourse of power during the 2024 Banten gubernatorial election using a Foucauldian critical perspective. For nearly two decades, political power in Banten was dominated by a dynastic network associated with Ratu Atut Chosiyah. However, the 2024 election marked a significant shift as the dynastic candidate was defeated by the Andra Soni–Ahmad Dimyati Natakusumah pair. This research aims to analyze how power discourse was constructed, how epistemic shifts occurred among the electorate, and how regimes of truth were produced through political communication. Employing a qualitative constructivist-critical approach, the study utilizes discourse analysis of campaign narratives, media content, and socio-political contexts. The findings reveal that the anti-corruption counter-narrative functioned as a strategic discursive formation that reconfigured public knowledge and delegitimized the dominant dynastic narrative. Social media amplification and the absence of explicit anti-corruption positioning from the dynastic camp strengthened this transformation. In Foucauldian terms, power operated as a strategy embedded in knowledge production, enabling voters to exercise agency through new regimes of truth at the polling booth. This study contributes theoretically by demonstrating the effectiveness of counter-narrative communication in disrupting entrenched political dynasties within democratic contexts and offers a model of discursive political communication for electoral transformation.